2020
DOI: 10.1007/s13300-020-00897-9
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between RDW, MPV and Weight Indices After Metabolic Surgery in Patients with Obesity and DM/IGR: Follow-Up Observation at 12 Months

Abstract: Introduction Red blood cell distribution width (RDW) and mean platelet volume (MPV) are both new biomarkers for the prognosis of many diseases. This study aimed to observe the predictive values of RDW and MPV for weight loss after different metabolic surgeries in patients with obesity and abnormal glucose metabolism [diabetes mellitus or impaired glucose regulation (DM/IGR)]. Methods We retrospectively analyzed the body weight (BW), body mass index (BMI) and blood routi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
2
0
0
Order By: Relevance
“…In our study, although there was no statistically significant difference in the group with B12 deficiency, we found that the mean MPV value increased, and the platelet count was lower than in the control group. This was in agreement with the work of Li et al This increase in MPV can be explained by the larger, newly synthesized young platelets to compensate for the decrease in platelets [20].…”
Section: Discussionsupporting
confidence: 93%
“…In our study, although there was no statistically significant difference in the group with B12 deficiency, we found that the mean MPV value increased, and the platelet count was lower than in the control group. This was in agreement with the work of Li et al This increase in MPV can be explained by the larger, newly synthesized young platelets to compensate for the decrease in platelets [20].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we also observed that patients with obesity had higher pre-operative RDW and NLR, which are risk factors for cardiovascular mortality described in previous studies (35)(36)(37). Their elevation may be associated with obesityrelated lower-grade chronic inflammation and inflammatory mechanisms of aortic dissection (38)(39)(40). Of note, despite the differences in baseline characteristics being unavoidable, gender, past medical history besides hypertension, surgical details, and treatment management did not differ between the two groups.…”
Section: Discussionsupporting
confidence: 76%
“…Other blood biomarkers were also considered as weight loss predictors after bariatric surgery; Wise ES et al showed that preoperative red blood cell distribution width (RDW), also a biomarker of inflammation and oxidative stress, is directly correlated with surgical success after laparoscopic Roux-en-Y gastric bypass one year after surgery [30]. Similar results were reported by others [31] as regards the role of preoperative RDW and mean platelet volume as predictors of weight loss after sleeve gastrectomy and bypass surgery.…”
Section: Discussionmentioning
confidence: 68%